Distributed consensus-based reactive power sharing in microgrids: A predictive virtual capacitance control technique. (October 2022) - Babayomi, Oluleke; Li, Yu; Zhang, Zhenbin
Abstract: In microgrids, multiple modular distributed generation (DG) are required to power the system's loads. Nonetheless, disproportionate reactive power ( Q ) sharing arises with unequal feeder line impedances of DGs connected to a common bus. Hence, this study proposes a novel method, based on virtual shunt and series capacitances, to regulate both accurate reactive power sharing, and at the same time restore the DG output voltages. The proposed method utilizes a dynamic average consensus algorithm for low-bandwidth communication among the neighbor DGs. The effectiveness of the control scheme is validated through stability analysis, extensive offline simulations and real-time hardware-in-the-loop tests on a microgrid system. Highlights: Shunt and series capacitances are emulated to restore VSC output voltages. Consensus-based dynamic compensation of feeder line impedance mismatches. Low communication requirements via distributed multiagent framework. Dynamic average consensus stability and consensus analyses for microgrid.